ENHANCEMENT OF SELEDRI SEED VIABILITY THROUGH EXTRACT EXTRACTS SEAWEED - Kosmas Ladora Gase; Tantri Palupi; Sri Rahayu (Jurnal Sains Pertanian Equator, 2018)
Celery seeds are seeds that choose dueti low viability becouse has hard seed shells, small buds and relatively recalcitrant seeds. This study aims to find out the best method to increase the viability of seeds of celery. This study used a Completely Randomized Design (CRD) with 6 treatments, namely (Soaking in Aquades), B (Soaking in Seaweed Extract 1,500 ppm), C (Soaking in Seaweed Extract 2,000 ppm), D (Soaking in Seaweed Extract 2,500 ppm), E (Soaking in Seaweed Extract 3,000 ppm), F (Soaking in Seaweed Extract 3,500 ppm). Each treatment used 50 celery seeds and consisted of 4 replications. The study was conducted in PKH Green Villa breeding. The results of this study indicate that the method of invigoration through soaking of seaweed extract had been able to increase viability of seeds of celery. Soaking in seaweed extract of 3,000 ppm was the best concentration to increase celery seed viability with 84,50% germination power germination, seed vigor reach 51.50%, growth rate 6.39% / etmal and similirity grow to 71,00%.   Keywords: Seed Celery, Immersion, Recruitment, Seaweed, Viability